SEQUENTIAL ISOLATION AND IDENTIFICATION OF HYDROCARBON DEGRADING BACTERIA FOR MICROBIAL ENHANCED OIL RECOVERY (MEOR) APPLICATION - Fahara, Tia
Microbial enhanced oil recovery (MEOR) is a cost-effective and ecofriendly process to retrieve unrecoverable oil from oil wells. Microbes that degrade heavy hydrocarbon fractions have been widely applied for MEOR. These bacteria can be obtained from sequential isolation. This study aimed to isolate and identify indigenous bacteria from West Java oil reservoir samples. This work demonstrates the sequential isolation method with different media and its SARA analysis of oil biodegradation after bacterial treatment. The degradation test of the SARA fraction (Saturated, Aromatic, Resinic, and Asphaltenes) at each isolation stage was gradually carried out by column chromatography and gravimetric methods. Isolation of the hydrocarbonoclastic bacteria was carried out in 2 stages at temperature 50°C in brine medium (2% yeast extract + sterile brine water + 2% non-sterile crude oil). A total of 39 isolates were obtained from two stage sequential isolation. The microscopic characteristics of the isolates showed the dominance of rod-shaped bacteria (bacilli) was 87.18% and Gram positive was 66.67% in both isolation stages. The results of the SARA degradation test showed a reduction in the asphaltene fraction of 2.58% in isolation stage I and 6.30% in isolation stage II, the reduction of the saturation fraction of 35.38% in isolation stage I and 25% in isolation stage II, while the fraction aromatic increased by 37.89% in isolation stage I and 32.11% in isolation stage II. The ability to grow at high temperature was screened in 50°C and obtained 22 bacterial isolates (56.41%) were thermophilic. Identification of hydrocarbonoclastic thermophilic indigenic bacterial isolates obtained by the MALDI-TOF MS method and identified 10 isolates as Bacillus licheniformis, 4 isolates as Bacillus cereus, 3 isolates as Bacillus pumilus, 2 isolates as Bacillus subtilis, 2 isolates as Bacillus fusiformis and 1 isolate isolates as Stenotrophomonas maltaphilia. Although only 6 bacterial species were identified, the 22 isolates had different characters and were confirmed by the emulsification index test which also had different values, so that it was probably different bacterial strains. Based on literature studies, the 6 bacteria identified from 22 isolates had the ability to degrade the heavy hydrocarbon fraction. Therefore, indigenous bacteria shows a potential application for MEOR.